Alcohol and premature death rates of the population of Tomsk Region - S. Yu. Kladov; I. N. Konobeyevskaya; R. S. Karpov (Бюллетень сибирской медицины)
The role of the alcoholic factor in structure of death rate of the population of Tomsk area is studied. At pathology-anatomic research alcohol in blood was found out in 38,9% of cases. This parameter remains rather stable during of some years while death rate from a poisoning with ethyl spirit last three years has decreased almost on third. The given parameter speaks about essential underestimation of the alcoholic factor in structure of death rate. At carrying out of examinations and researches of corpses of nonviolent death ethyl spirit has been found out in 18,4%. These data draw attention to alchohol-dependent diseases of internal bodies. Other picture comes to light at the analysis of the alcoholic factor in structure of violent death rate. For 2007 at carrying out of examinations and researches of corpses of a violent death ethyl spirit has been found out in 63,2% of cases. The greatest contribution of the alcoholic factor is revealed at such reasons of death, as a poisoning with carbonic oxide (69,7%), action of low temperatures (67,4%), road and transport incidents (48,5%).